2015
DOI: 10.1002/jcp.25135
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta‐Analysis: Circulating miRNAs for Diagnosis of Hepatocellular Carcinoma

Abstract: Because early-stage hepatocellular carcinoma (HCC) is difficult to diagnose using the existing techniques, identifying better biomarkers would likely improve the patients' prognoses. We performed a systematic review and meta-analysis of published studies to appraise the utility of microRNAs (miRNAs) for the early diagnosis of HCC. Pertinent literature was collected from the Medline, Embase, and Chinese National Knowledge Infrastructure databases. We analyzed 50 studies that included 3423 cases of HCC, 2403 chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 53 publications
4
69
0
2
Order By: Relevance
“…Moreover, exosomal miRNA-21 has been considered as potential biomarker of cancer [349]. Furthermore, increased expression of circulating miRNA-21 has been reported in patients with breast cancer [350], lung cancer [350], colorectal carcinoma [350], and hepatocellular carcinoma [351,352,353]. Hepatocellular carcinoma has recently been related to increased consumption of cow’s milk [354].…”
Section: Milk-mediated Epigenetic Signaling and Diseases Of Civilmentioning
confidence: 99%
“…Moreover, exosomal miRNA-21 has been considered as potential biomarker of cancer [349]. Furthermore, increased expression of circulating miRNA-21 has been reported in patients with breast cancer [350], lung cancer [350], colorectal carcinoma [350], and hepatocellular carcinoma [351,352,353]. Hepatocellular carcinoma has recently been related to increased consumption of cow’s milk [354].…”
Section: Milk-mediated Epigenetic Signaling and Diseases Of Civilmentioning
confidence: 99%
“…The combination of miR-21 and AFP increased its diagnostic value (more than 90%) suggesting its potential use as a biomarker of HCC diagnosis [125] . A systematic review and meta-analysis concluded that circulating miRNAs, particularly miR-21 and miR-122 are promising biomarkers for the early diagnosis of HCC [126] . In addition, miR-21 (oncogene) and miR-182 (tumor suppressor gene) were related with the development of metastasis [127,128] .…”
Section: Circulating Mirnasmentioning
confidence: 99%
“…More experimentation is required in this direction [155]. Validating a certain miRNA or miRNA sets, as non-invasive biomarker(s) in patients suffering from OA or gouty arthritis, using an established statistical method, such as receiver operating characteristic (ROC) curve analysis as has been attempted in other diseases [156,157], would therefore be another future goal. For instance, miRNA let-7e seems to be a negative predictor for severe OA, at least in Caucasians [155], and its validation as a biomarker is of great interest.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%